Chitosan microcarriers in mammalian cell culture - Hussein, Abeir; Hashim, Yumi Zuhanis Has-Yun; Mohd. Salleh, Hamzah (2014)
Chitosan is a naturally-occuring biomaterial with many advantages, including being non-toxic, biocompatible and biodegradable. It has a wide range of applications due to its numerous properties, and thus finds uses in wound dressings, biopesticides, tissues engineering, and pharmaceuticals. Chitosan microspheres have been produced via a variety of tehniques that exploit the different properties of chitosan, espeecially its gelling properties, and do so with the intended application in mind. These techniques are often discussed in light of their use as drug carriers. As such, chitosan has not received much attention as a microcarrier substrate for cell culture. This review provides and indight into the various reported techniques of production of chitosan microspeheres for use in mammalian cell culture and highlights recent findings of the evaluation of chitosan as a microcarrier substrate.